Intellectual Property Rights and Their Inheritance: Positive Law and Islamic Law Perspectives - Fauzy, Addyn Daffa; Ichsan, Muchammad (Media of Law and Sharia, 2026)
Recently, disputes regarding intellectual property rights (IPR) have frequently arisen within society. This is particularly true for IPR, which are intangible assets that hold significant economic value and are inherited after the owner's death. This study aims to examine the status of IPR as movable property and an object of inheritance based on Indonesian positive law and Islamic law. Using a normative-juridical and comparative law approach, this study analyzes seven IPR laws (the Copyright Law, the Patent Law, the Trademark and Geographical Indications Law, the Trade Secrets Act, the Industrial Design Act, the Integrated Circuit Layout-Design Act, and the Plant Variety Protection Act) as well as the Civil Code, the Compilation of Islamic Law, and fiqh doctrines on inheritance. Research findings indicate that Indonesian positive law explicitly recognizes IPR as inheritable property that can be transferred to heirs through registration (copyrights, patents, trademarks, and others). Meanwhile, Islamic law recognizes IPR as māl (property) that can be owned and inherited, provided it meets the requirements of perfect ownership and does not conflict with Sharia. The integration of these two legal systems enables Muslims in Indonesia to inherit IPR in accordance with the principles of justice and benefit.